2020
DOI: 10.9789/2175-5361.rpcfo.v12.8527
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of nursing professionals and the implementation of hospital humanization policy

Abstract: Objetivo: Conhecer a produção cientifica no período de 2013 a 2018, acerca dos comportamentos dos profissionais de enfermagem para efetivação da humanização hospitalar. Método: Trata-se de uma revisão integrativa da literatura realizada através das bases de dados SciELO, LILACS, IBECS, MEDLINE e Biblioteca Cochrane. A busca foi realizada em outubro de 2018, possuindo como amostra final 20 artigos. Resultados: Observou-se, após leitura na integra, a delimitação de 3 eixos temáticos quanto ao empoderamento profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
(12 reference statements)
2
5
0
Order By: Relevance
“…The present study also found that medical humanization has the influence on doctor–patient communication, which is consistent with the previous literature ( 46 , 63 , 64 ). For example, Basile et al ( 65 ) found that dehumanization was perceived by patients in the “communication” when medical workers talked “over” patients and made distressing remarks in front of patients.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The present study also found that medical humanization has the influence on doctor–patient communication, which is consistent with the previous literature ( 46 , 63 , 64 ). For example, Basile et al ( 65 ) found that dehumanization was perceived by patients in the “communication” when medical workers talked “over” patients and made distressing remarks in front of patients.…”
Section: Discussionsupporting
confidence: 93%
“…Poor patient physician communication decreases patient compliance to treatment strategies, patient satisfaction scores and on the extreme leads to violence directed to physicians ( 66 ). In humanized care, communication is an effective tool for establishing a good relationship between medical professionals and patients ( 46 ). To be humanized as medical staff and make patients perceive the medical humanization well call for effective communication ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations